Physical and mechanical properties of woven kenaf/bamboo fiber mat reinforced epoxy hybrid composites - Ismail, Ahmad Safwan (North Carolina State University, 2019)
Research interest has shifted from synthetic fiber to natural fiber due to environmental concerns and government regulation. This study evaluated the physical and mechanical properties of kenaf(K)/bamboo(B) fiber mat reinforced epoxy hybrid composites. Kenaf, bamboo, and kenaf/bamboo hybrid composites were prepared using the hand lay-up method at 40% wt total fiber loading. Different ratios of kenaf to bamboo fibers, such as 70:30(3B7K), 50:50(BK), and 30:70(7B3K), were used to fabricate the hybrid composites. Kenaf composite and bamboo composite were fabricated as controls. Mechanical (flexural and impact), morphological, and physical properties (thickness swelling, water absorption, and density) were examined. The density, water absorption and thickness swelling of the composites increased as the kenaf weight ratio increased. The flexural properties of kenaf composites were improved by hybridization with bamboo fiber, whereas the impact properties of bamboo were improved by hybridization with a woven kenaf mat. Hybrid composites with a 50:50 ratio showed the highest flexural and impact strength. Scanning electron microscopy (SEM) of flexural fracture showed that 50:50(BK) displayed better interfacial adhesion than the other two ratios. The woven kenaf/bamboo hybrid composite is suitable for use in the fabrication of automotive components.